Dampak Kebiasaan yang Bisa Mengganggu Kenyamanan Tetangga dengan Melakukan Karaokean dengan Suara Keras - Ageng Saepudin Kanda; Siti Anggia Denisa (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
With neighborly harmony, a harmonious society will be created, looking after each other, respecting each other, and also helping each other. An unpleasant act is an action that disturbs public order. Unpleasant actions usually take the form of criminalization or activities that are considered to be detrimental to people or the public. Living in harmony with neighbors will make you feel comfortable and happy. The aim of this research is to find out the impact of habits that can disturb the comfort of neighbors around the BATUJAJAR transit apartment, Giriasih village, West Bandung Regency. The research method used is a descriptive qualitative research method, where the data produced is a description of the results of observations at the location and the results of interviews with the surrounding community who are the objects as sources. From the results of observations made, the impact caused by neighbors' habit of frequently karaoke at night is that it creates disharmony between neighbors, causes discomfort when living next door, and really disturbs neighbors with sound police.